2013
DOI: 10.3346/jkms.2013.28.9.1356
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Clinical Characteristics, and Management of Functional Constipation at Pediatric Gastroenterology Clinics

Abstract: The purpose of this study was to investigate the prevalence, clinical characteristics, and management of functional constipation at pediatric gastroenterology clinics. A prospective survey using the Rome III criteria was distributed to a group of parents of children with a constipation history and its control group in May 2008. The mean prevalence of constipation was 6.4%, which was similar to those in other countries. Statistically significant variables for children without constipation were that more childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
34
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 21 publications
6
34
5
Order By: Relevance
“…The mean age of the constipated children in our study was 4.8 years, which was comparable with the results of other studies (10,11). However, the children's mean age was higher in the studies performed by Inan et al (12) and Faleiros et al (13).…”
Section: Discussionsupporting
confidence: 81%
“…The mean age of the constipated children in our study was 4.8 years, which was comparable with the results of other studies (10,11). However, the children's mean age was higher in the studies performed by Inan et al (12) and Faleiros et al (13).…”
Section: Discussionsupporting
confidence: 81%
“…The same has been reported in another study carried out in Korea (14) . On the other hand, Minkyu Park et al reported that 500 ml or less of daily water intake was significantly associated with functional constipation (15) .…”
supporting
confidence: 71%
“…In Northern areas of China, among children aged 4 -14 year, the prevalence of functional constipation was 4.7% with high prevalence in the age group 4 -6 years (12) . In USA, among children up to three years of age, 27.1% had at least one functional gastrointestinal disorder (13) .In Korea, among children ages at least 12 months the prevalence range was from 1.8% to 13.9% (14). The variation between prevalence rates of functional constipation among children in the aforementioned studies including ours could be mainly attributed to apparent difference in the age group of the studied population.…”
Section: Discussion:-mentioning
confidence: 55%
See 2 more Smart Citations